Attitudes of Education College Students Towards the Teaching Profession in the City of Misrata - Al-Shawki, Ahmed Mohammed; Karim, Rabia Ahmed ((Faculty of Arts Journal) مجلة كلية الآداب - جامعة مصراتة, 2018)
Teaching is described as one of important occupations and which plays an essential role in the prosperity of a society. If this job has not been promoted, there will not be specialists or experts in the different life aspects and all the society basic needs will be difficult to meet. In regard to this teachers’ goals and students’ attributes and needs had better be considered. The current study aims to find out the attributes of Faculty of Education students towards teaching as an occupation and how gender difference can affect the students’ attributes. This study is significant as it might provide the students positive views about teaching. Also, the results of the study may help teachers to perform more effectively. Educational instructions may benefit from this study findings as they can be a benchmark or a criterion to have a reasonable knowledge of the students’ attributes. To analyze the data of the study, the researcher used some statistical tools which were T-test, Percentage, the Mean and Standard deviation. The findings of the study revealed that Faculty of Education students have positive attitudes towards teaching. However, it appears that female students outweigh the male students.